A Preliminary Evaluation of Variability, Genetic Estimates, and Association among Phenotypic Traits of African Yam Bean Landraces from Ghana - Remember Roger Adjei; Esther Fobi Donkor; Kwadwo Gyasi Santo; Charles Adarkwah; Amanda Sarfo Boateng; Daniel Ntiamoah Afreh; Edward Sallah (Advances in Agriculture)
A field experiment was conducted at the Research and Teaching Farm, School of Agriculture and Technology (SOAT), University of Energy and Natural Resources (UENR), Dormaa Ahenkro Campus, Ghana, to determine the genetic variability, heritability, genetic advance, and correlation among growth and yield traits of the African yam bean in Ghana. There were significant differences (p<0.05) for the traits studied, except for days to 50% emergence, petiole length, days to maturity, stem diameter, days to 50% flowering, pod weight, pod beak length, pod weight per plant, seed length, and seed width. The phenotypic coefficient of variation and genotypic coefficient of variation for the yield and yield components ranged from 9.43% to 18.92% and 3.25% to 15.93%, respectively, and from 9.35% to 20.08% and 2.15% to 23.28%, respectively, for the growth parameters. Heritability ranged from 34.54% to 91.81, and the GAM ranged from 2.77% to 45.96% for the growth parameters. The heritability and GAM for the yield parameters ranged from 11.85% to 73.56% and 1.94% to 27.64%, respectively. The correlation analysis revealed a positive and highly significant (p<0.001) relationship between petiole length and leaf length (r = 0.573), number of seeds per pod and number of leaves (r = 0.520), pod beak length and peduncle length (r = 0.560), pod weight per plant and pod weight per plot (r = 0.971), seed weight per plant and 100 seed weight (r = 0.967), grain yield and 100 seed weight (r = 0.999) and seed weight per plant (r = 0.970), 100 seed weight and pod per plant (r = 0.576). The study revealed diversity among the AYB landraces collected, which provides an opportunity for improvement of the African yam bean in Ghana. There is the need for the conservation of these landraces for further evaluations and the improvement of the promising landraces and traits through breeding programmes.